Correcting Mistakes: Protecting Medical Education from Publishing Barriers: Correcting Mistakes Protecting Medical Education - Ulusu, Nuriye Nuray (Journal of Medical Biochemistry, 2026)
Medical education is increasingly shifting from traditional textbooks toward research and review articles and electronic textbooks. Research articles and reviews are preferred, especially in postgraduate education and in lectures in medicine. Research articles and reviews play an important role in postgraduate education by helping students, assistants, and educators learn novel scientific developments. Therefore, maintaining the accuracy of research articles is essential. The scientific mistakes are generally found in articles that were previously published with old technology and written with limited internet access before online publications. If a journal refuses to correct a biological error, the incorrect information may continue to be cited, contributing to spreading misinformation that affects future meta-analyses and clinical guidelines. Such situations may negatively affect the reliability of scientific literature. In this comment paper, we are proposing a Correction Integrity Score (CIS), which can be used by the journals’ editorial systems to support the transparent correction of verified errors. Correction mechanisms should be accessible, transparent, and independent from various factors. The score would be usable like an impact factor of the journal, and using a correction score makes the publisher more reliable, ethical, and economical for future research.